Cracking the code: Problems and possibilities of curriculum analysis in adult education - Ralf St. Clair (Adult Education Research Conference, 2001)
In this paper I argue for the importance of explicit curriculum analysis as a critical approach to adult education research, and highlight several intriguing and challenging aspects of the endeavour. The discussion is illustrated with examples from my own work on the structures of knowledge in our vocation.